Durability of glycaemic efficacy over 2 years with dapagliflozin versus glipizide as add‐on therapies in patients whose type 2 diabetes mellitus is inadequately controlled with metformin†. Issue 11 (10th July 2014) - Nauck, M. A.; Del Prato, S.; Durán‐García, S.; Rohwedder, K.; Langkilde, A. M.; Sugg, J.; Parikh, S. J.
<x xml:space="preserve">Abstract</x> Aims To assess the long‐term glycaemic durability, safety and tolerability of dapagliflozin versus glipizide as add‐on therapies in patients with type 2 diabetes inadequately controlled by metformin alone. Methods This was a 52‐week, randomised, double‐blind study of dapagliflozin (n = 406) versus glipizide (n = 408), uptitrated over 18 weeks according to tolerability and glycaemic response to a maximum of 10 and 20 mg/day, respectively, as add‐on therapies to metformin (≥1500 mg/day) with a 156‐week double‐blind extension period. Data over 104 weeks are reported here. Results In total, 53.1% of patients completed 104 weeks of treatment. After the greater initial decrease (0–18 weeks) in glycated haemoglobin (HbA1c) with glipizide, the 18–104‐week HbA1c coefficient of failure (CoF) was lower with dapagliflozin (0.13%/year) than with glipizide (0.59%/year), resulting in significant dapagliflozin versus glipizide differences of −0.46%/year (95% CI −0.60, −0.33; p = 0.0001) for CoF and −0.18%(−2.0 mmol/mol) [95% CI −0.33(−3.6), −0.03(−0.3); p = 0.021] for 104‐week HbA1c. Dapagliflozin produced sustained reductions in weight and systolic blood pressure, whereas glipizide increased weight and systolic blood pressure, giving 104‐week dapagliflozin versus glipizide differences of −5.1 kg (95% CI: −5.7, −4.4) and −3.9 mmHg (95% CI: −6.1, −1.7), respectively. Over 104 weeks, the hypoglycaemia rate was 10‐fold lower with dapagliflozin than with glipizide (4.2 vs. 45.8%), whereas patient proportions with events suggestive of genital infection and of urinary tract infection (UTI) were greater with dapagliflozin (14.8 and 13.5%, respectively) than with glipizide (2.9 and 9.1%, respectively). Conclusions Over 2 years, compared with glipizide, dapagliflozin demonstrated greater glycaemic durability, sustained reductions in weight and systolic blood pressure and a low hypoglycaemia rate; however, genital infections and UTIs occurred more frequently.